2021
DOI: 10.1292/jvms.20-0409
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological changes in the pancreas due to decreased pancreatic blood flow in a canine tachycardia-induced cardiomyopathy model

Abstract: In dogs, pancreatic acinar cell injury is thought to be caused by decreased pancreatic blood flow due to heart failure. In previous our report, it demonstrated that decreased heart function causes a significant decrease in pancreatic blood flow in heart failure dog model caused by rapid ventricular pacing (RVP). However, the types of histopathological changes remain unclear. We aimed to verify the types of histopathological changes occurring in the pancreatic tissue due to decreased heart function. After RVP f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 12 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…Histopathological examination showed no changes in pancreatic tissue containing pancreatic acinar cells in the pimobendan group, in which CO and PBF were maintained. In contrast, in the control group, similar to previous reports, pancreatic acinar cell atrophy with a decrease in zymogen granules, and thus the trypsinogen contained therein, was observed over a wide area of the pancreas (7). Therefore, we concluded that a decrease in PBF was a direct cause of pancreatic acinar cell atrophy.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Histopathological examination showed no changes in pancreatic tissue containing pancreatic acinar cells in the pimobendan group, in which CO and PBF were maintained. In contrast, in the control group, similar to previous reports, pancreatic acinar cell atrophy with a decrease in zymogen granules, and thus the trypsinogen contained therein, was observed over a wide area of the pancreas (7). Therefore, we concluded that a decrease in PBF was a direct cause of pancreatic acinar cell atrophy.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of the study clarified that a decrease in CO lowers blood pressure and reduces PBF (6). Furthermore, examination of the pancreatic tissue revealed that pancreatic acinar cell atrophy, which is a change in the prestage of pancreatitis, was caused (7). However, the mechanism by which RVP causes pancreatic acinar cell atrophy in dogs remains unknown.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Interestingly, this disproportionality is partially reversible with pharmacological renin-angiotensin inhibition [ 57 ]. Histopathological follow-up analyses of pancreatic tissue in the abovementioned dog model demonstrated atrophy of the acinar cells specifically [ 58 , 59 ], indicating that an association between the hemodynamic perturbations of heart failure and loss of exocrine parenchyma exists.…”
Section: Studies On Pancreatic Injury In Heart Failurementioning
confidence: 99%